2021
DOI: 10.1186/s12884-021-03721-9
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for non-adherent retained placenta after vaginal delivery: a systematic review

Abstract: Background Retained placenta represents a cause of maternal morbidity and mortality affecting 0.5–3% of all vaginal deliveries. The unpredictability of this condition makes difficult to develop predictive and preventive strategies to apply in clinical practice. This analysis collected and analyzed all known risk factors related to this obstetric complication. Methods A systematic literature review for all original research articles published betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
(13 reference statements)
3
4
0
1
Order By: Relevance
“…The effect of maternal age on PPH caused by atony are in line with existing knowledge [2,4,6,7,32]. Studies on associations between maternal age and other types of PPH are scarce, but an association with retained placenta in general has been reported [32]. Parity had strongest effect on PPH due to dystocia; 76% of the cases were primiparas, which agrees with the higher risk of dystocia in nulliparas [33].…”
Section: Plos Onesupporting
confidence: 82%
See 1 more Smart Citation
“…The effect of maternal age on PPH caused by atony are in line with existing knowledge [2,4,6,7,32]. Studies on associations between maternal age and other types of PPH are scarce, but an association with retained placenta in general has been reported [32]. Parity had strongest effect on PPH due to dystocia; 76% of the cases were primiparas, which agrees with the higher risk of dystocia in nulliparas [33].…”
Section: Plos Onesupporting
confidence: 82%
“…Our results confirm that maternal age was associated with all types of PPH (with the strongest association for PPH caused by dystocia). The effect of maternal age on PPH caused by atony are in line with existing knowledge [2,4,6,7,32]. Studies on associations between maternal age and other types of PPH are scarce, but an association with retained placenta in general has been reported [32].…”
Section: Plos Onesupporting
confidence: 81%
“…Our finding that stillbirth is associated with an elevated risk of curettage (the second most common SMM item in our study which was not included in the CDC composite) is in keeping with an increased risk of retained placenta following stillbirth [10,31,32]. Other risk factors for retained placenta that make stillbirths more at-risk include early preterm birth [31,33], preeclampsia and foetal growth restriction [34].…”
Section: Discussionsupporting
confidence: 75%
“…For the analyses in this table, we removed 21 cases in which pregnant patients exited the public health system before giving birth. We also removed 5 cases with extensive missing data b National rates reported in this column were obtained by request from the El Salvador Sistemas Estadísticas de Salud under the Salvadoran Law on Access to Public Information and include the same 6-year average (2013–2018) as our study population c National rates reported in this column were obtained by request from the El Salvador Sistema de Morbimortalidad en Línea (SIMMOW) under the Salvadoran Law on Access to Public Information and contained all births treated at the national hospitals within MINSAL (Ministerio de Salud El Salvador) and include the same 6-year average (2013–2018) as our study population, except when specified otherwise d Estimated pooled prevalence for the Latin American Region per a 2012 analysis of existing studies 18 e Reported incidence of maternal infections in the United States as reported in a 2013 study of 1,001,189 deliveries at 355 US hospitals 19 f Estimated pooled prevalence for the Americas region according to a 2013 analysis of existing studies 20 g Estimated pooled prevalence of gestational diabetes mellitus in middle income countries according to a 2021 analysis of existing studies 21 h The World Health Organization's (WHO) estimated prevalence of anemia in pregnant women in Latin America for 1993 to 2005 22 i Estimated prevalence of polyhydramnios in all pregnancies 23 j Estimated prevalence of PROM in the United States 24 k Estimated prevalence or PPROM in the United States 24 l Estimated prevalence of retained placenta in all pregnancies 25 m Because of missing data in 2013 and 2014, this statistic only includes averaged data from 4 years (2015–2018) n Estimated pooled prevalence for 8 nations according to a 2015 analysis of existing studies 26 …”
Section: Resultsmentioning
confidence: 99%